PENGARUH THINK PAIR AND SHARE TERHADAP PEMAHAMAN AKIDAH AKHLAK SISWA SMA - Maulidiya Zumrotul Chiqmiya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the low level of students’ understanding in the Akidah Akhlak subject, especially on commendable and reprehensible morals material at SMA An-Najiyah Surabaya. One effort to improve students’ understanding is by implementing the cooperative learning model of Think Pair and Share (TPS). This study aimed to determine the effect of the Think Pair and Share learning model on improving students’ understanding in terms of students’ cognitive styles. This research used a quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 18 tenth-grade students of SMA An-Najiyah Surabaya. Data collection techniques were conducted through tests and questionnaires. Data analysis was carried out using IBM SPSS Statistics version 25 including descriptive statistical analysis, validity test, reliability test, Shapiro-Wilk normality test, and Wilcoxon Signed Rank Test. The results showed that the average pretest score of 67.33 increased to 92.78 in the posttest. The Wilcoxon test result obtained an Asymp. Sig. (2-tailed) value of 0.001 < 0.05, indicating a significant effect of the Think Pair and Share learning model on improving students’ understanding of commendable and reprehensible morals material. Therefore, the TPS learning model can be used as an effective alternative learning model to improve students’ understanding in Akidah Akhlak subjects. ABSTRAK Penelitian ini dilatar belakangi oleh rendahnya pemahaman siswa pada mata pelajaran Akidah Akhlak, khususnya materi akhlak terpuji dan akhlak tercela di SMA An-Najiyah Surabaya. Salah satu upaya yang dapat dilakukan untuk meningkatkan pemahaman siswa adalah dengan menerapkan model pembelajaran kooperatif tipe Think Pair and Share (TPS). Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Think Pair and Share terhadap peningkatan pemahaman siswa ditinjau dari gaya kognitif siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain One Group Pretest-Posttest Design. Sampel penelitian berjumlah 18 siswa kelas X SMA An-Najiyah Surabaya. Teknik pengumpulan data dilakukan melalui tes dan angket. Analisis data menggunakan bantuan IBM SPSS Statistics versi 25 meliputi analisis statistik deskriptif, uji validitas, uji reliabilitas, uji normalitas Shapiro-Wilk, dan uji hipotesis Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa nilai rata-rata pretest sebesar 67,33 meningkat menjadi 92,78 pada posttest. Hasil uji Wilcoxon memperoleh nilai Asymp. Sig. (2-tailed) sebesar 0,001 < 0,05 yang menunjukkan adanya pengaruh signifikan model pembelajaran Think Pair and Share terhadap peningkatan pemahaman siswa pada materi akhlak terpuji dan akhlak tercela. Dengan demikian, model pembelajaran TPS dapat dijadikan alternatif pembelajaran yang efektif dalam meningkatkan pemahaman siswa pada mata pelajaran Akidah Akhlak.